Analisis Kekeliruan Berbahasa Indonesia dalam Tataran Fonologi oleh Penutur Asing pada Kanal YouTube IShowSpeed - Muhammad Nazar Al Azhari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Several pronunciation faults in the Indonesian language and one in the Javanese language are to be examined in this study, which is based on a phonological analysis of the YouTube channel